Cumulative exposure to metabolic syndrome increases thyroid cancer risk in young adults: a population-based cohort study - Jinyoung Kim; Kyungdo Han; Mee Kyoung Kim; Ki-Hyun Baek; Ki-Ho Song; Hyuk-Sang Kwon (The Korean Journal of Internal Medicine, 2023)
Background/Aims A re-increasing trend of thyroid cancer since 2015 has been observed despite a similar examination rate, and the incidence of thyroid cancer among young adults continues to rise. Methods This study used data from the Korean National Health Insurance Service. Individuals 20–39 years of age who underwent ≥ 4 health checkups from 2009–2013 were enrolled and followed throughout 2019. To quantify the metabolic burden, groups were divided by the number of diagnoses of metabolic syndrome across four consecutive health examinations. Results Among the study population (n = 1,204,646), 5,929 (0.5%) were diagnosed with thyroid cancer during a follow-up period of 5 years. The hazard ratio (95% confidence interval) values of thyroid cancer occurrence according to the number (1–4) of diagnoses of metabolic syndrome across the four health examinations compared to the group without met-abolic syndrome were significantly greater, as follows: 1.12 (1.02–1.23), 1.25 (1.10–1.42), 1.33 (1.15–1.55), and 1.48 (1.25–1.75) (p for trend < 0.01), respectively. Each component of metabolic syndrome showed a significant increase in hazard ratio according to the number of diagnoses except for impaired fasting glucose criteria. Conclusions Cumulative exposure to metabolic syndrome was associated with thyroid cancer risk in young adults.